IMPLYING MEANING: AN ANALYSIS OF DECLARATIVE UTTERANCES AS INDIRECT SPEECH ACTS - Darmanto, Darmanto; Muliawan, Anugrah Adi; Cahyo, Eko Nur; Maulidita, Salismi Zulfi (Jurnal Multidisipliner Kapalamada, 2025)
The present study aims at examining the use of declarative utterances for implying meaning. This study is qualitative research in which the data are gathered from the subtitle movie “Knight and Day and Day” consisting of declarative sentences. The findings reveal several examples in which declarative utterances are used to imply meaning, suggesting that language has more purpose than simple information exchange. Declarative sentences are not only employed as statements of fact but also as veiled requests or subtle commands. This highlights the dynamic nature of communication, where the intended meaning can differ significantly from the literal words spoken. Listeners cannot just assume that speakers always express themselves literally. Often, the meaning is layered and nuanced, thus requiring the listeners to consider not only the words themselves but also the surrounding contexts. This study suggests that individuals should be aware of the potential meaning implied in speech and seek to understand the speaker’s intended message.